МАЙЛЫ ДАҚЫЛДАРДЫҢ СОРТТАРЫН БІРТЕКТІЛЕУДЕГІ БЕЛОКТЫҚ МАРКЕРЛЕР (Experimental biology, 2015)
The results of oilseed crops (safflower, canola and sunflower) varieties identification on the spectra of storage proteins are given. Informative zones of components for each culture were determined, the degree of intra varieties polymorphism and ratio of biotypes were established.
Keywords: oilseed crops